Value of the clinical pharmacist interventions in the application of the American College of Cardiology (ACC/AHA) 2018 guideline for cholesterol management - AlAhmad, Mohammad M; ZainAlAbdin, Sham; AlAhmad, Khozama; AlAhmad, Iqbal; AbuRuz, Salah (PloS one, 2023)
OBJECTIVES: The study aims to examine the extent to which the updated ACC/AHA management of blood cholesterol guideline (2018) is implemented in practice and to assess the value of the clinical pharmacist interventions in improving physicians' adherence the guidelines recommendations. METHODS: We utilized in this study an interventional before-after design. The study was conducted on 272 adult patients who visited the study site internal medicine clinics and were candidates for statin therapy based on the 2018 ACC/AHA guidelines for cholesterol management. Adherence to guideline recommendations was measured before and after clinical pharmacists' interventions by calculating the percentage of patients receiving statin therapy as per guideline recommendation, the type and intensity (moderate or high intensity) of statin therapy used, and the need for additional non-statin therapy. RESULTS: Adherence with guideline recommendations was significantly improved from 60.3% to 92.6% (X2 = 79.1, p = 0.0001) after clinical pharmacist interventions. Among patients who were on statin therapy, the percentage of those who were on proper statin intensity increased significantly from 47.6% to 94.4% (X2 = 72.5, p = 0.0001). The combination of statins with non-statin therapies such as ezetimibe and PCSK9 inhibitors increased from 8.5% to 30.6% (X2 = 95, p<0.0001) and from 0.0% to 1.6% (X2 = 6, p = 0.014), respectively. The use of other lipid-lowering agents was diminished from 14.6% to 3.2% (X2 = 19.2, p<0.0001). CONCLUSION: Collaboration between physicians and clinical pharmacists is a crucial strategy to improve patients' treatment and hence, achieve better health outcomes among patients suffering from dyslipidemia.
Keywords: hypercholesterolemie; kardiovaskulární nemoci; United States; dodržování směrnic; Spojené státy americké; kardiologie; lidé; Adult; Hypercholesterolemia; dospělí; Guideline Adherence; Cholesterol; Proprotein Convertase 9; Cardiology; Pharmacists; Humans; proproteinkonvertasa subtilisin/kexin typu 9; farmaceuti; cholesterol; statiny; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Cardiovascular Diseases